Reading, an inclusive process in the multigrade classroom - Chaparro, Rudth (Universidad Pedagógica y Tecnológica de Colombia, 2022)
This article reflects on the experience of teaching and learning reading with children considered inclusive in a multigrade classroom. A qualitative interpretative approach was used. The results show the importance of accepting the plurality of meanings that a text can have according to the particular reading experience of each child. Teaching practices do not yet orient reading as the enjoyment of a personal space, but are based on the design of playful strategies for the comprehension of meanings, which excludes the understanding of the realities, interests and needs of the students.